1996
DOI: 10.1097/00000539-199601000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Gas Embolism by Transesophageal Echocardiography During Laparoscopic Cholecystectomy

Abstract: Using transesophageal echocardiography (TEE), 16 patients (ASA physical status I-III), undergoing laparoscopic cholecystectomy, were assessed for the occurrence of episodes of gas embolism and cardiovascular changes related to those emboli. The long-axis four-chamber view was monitored continuously, except for predetermined intervals where the transgastric short-axis view was obtained to derive the end-diastolic area (EDA), the end-systolic area (ESA), and the ejection fraction (EF). In one patient, we monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 27 publications
1
31
1
Order By: Relevance
“…Intravascular presence of small amounts of soluble gas like CO 2 probably occurs frequently without having any clinical consequence, whereas large amounts of a soluble gas or smaller amounts of an insoluble gas (air, nitrous oxide) may cause death. When studied with transesophageal echocardiography, 68% of asymptomatic patients have CO 2 bubbling in the right chamber of the heart during laparoscopic cholecystectomy [50]. Transcranial Doppler experiments have shown that CO 2 bubbles may even reach the cerebral circulation [2].…”
Section: Gas Embolismmentioning
confidence: 99%
“…Intravascular presence of small amounts of soluble gas like CO 2 probably occurs frequently without having any clinical consequence, whereas large amounts of a soluble gas or smaller amounts of an insoluble gas (air, nitrous oxide) may cause death. When studied with transesophageal echocardiography, 68% of asymptomatic patients have CO 2 bubbling in the right chamber of the heart during laparoscopic cholecystectomy [50]. Transcranial Doppler experiments have shown that CO 2 bubbles may even reach the cerebral circulation [2].…”
Section: Gas Embolismmentioning
confidence: 99%
“…The risk of AE is well recognized in procedures in which the operative site is above the level the heart, classically with neurosurgical cases performed in the sitting position[1] or otolaryngologic surgeries[2] but could happen in various clinical settings such as laparoscopic surgery,[34] pelvic procedures,[5] endoscopic saphenous vein harvesting,[6] and orthopedic procedures. [7] AE during sigmoidoscopy or colonoscopy is a rarely reported complication.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical signs like "mill-wheel" murmur or a decrease of E T CO 2 are useful for detection of VAEs, TEE is widely regarded as the most sensitive means of detection, and can identify bubbles as small as 20-50 碌m in diameter [12,13]. TEE is much more effective than other technology at detecting PAEs, because it is hard to assess the passage of air bubbles to systemic circulation by other methods.…”
Section: Discussionmentioning
confidence: 99%